Anilido-imine zinc complexes: Efficient catalysts for ring-opening polymerization of L-lactide - Yao, Wei; Cui, Ning; Xue, Ying-zhao; Liu, Tian-tian; Wang, Yan (Chemical research in Chinese universities, 2013)
A series of anilido-imine zinc complexes ortho -C 6 H 4 (CH=NAr)(NAr)ZnEt[Ar=2,6-Me 2 C 6 H 3 ( 2 a); Ar=2,6-Et 2 C 6 H 3 ( 2 b)] was synthesized, characterized and used as catalysts for the ring-opening polymerization of L -lactide in the presence of benzyl alcohol. The effects of the structures of catalysts and reaction conditions on the reactivity were investigated. The polymerization of L -lactide initiated by each of these complexes was found to take place with a controlled manner.